2021
DOI: 10.1039/d0ra10728j
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and evaluation of novel indole-2-carboxamides for growth inhibition of Mycobacterium tuberculosis and paediatric brain tumour cells

Abstract: In this study, we demonstrated that an indoleamide scaffold can be fine-tuned to confer a set of derivatives with selective antitubercular and/or antitumour activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Sredni et al have identified mycobacterial membrane protein large 3 transporter (mmpL3) as a target for indole-2-caboxamides (5-7, Figure 4) with anti-TB activity (MIC) in the range of 0.32-0.70 μM against drug sensitive Mtb, wherein the best active compound 6 showed minimum cytotoxicity with the IC 50 of 40.9 μM and selectivity index (SI) of 128 against Vero cell lines. [37] Further, the compound (5) were evaluated for cytotoxicity screening against glioblastoma multiforme (GBM) cell lines (KNS42) with IC 50 (viability) of 0.84 μM. A docking examination was performed using compounds 5 and 6 to reveal the binding mode of the N-rimantadine indoleamides against mmpL3 (PDB ID: 6AJJ) and they were found to make the hydrogen bonds (HBs) with the Asp645 through their nitrogen of carboxamide and indole moieties, having similar binding modes with the previously identified carboxamides ICA-38.…”
Section: Indolesmentioning
confidence: 99%
See 2 more Smart Citations
“…Sredni et al have identified mycobacterial membrane protein large 3 transporter (mmpL3) as a target for indole-2-caboxamides (5-7, Figure 4) with anti-TB activity (MIC) in the range of 0.32-0.70 μM against drug sensitive Mtb, wherein the best active compound 6 showed minimum cytotoxicity with the IC 50 of 40.9 μM and selectivity index (SI) of 128 against Vero cell lines. [37] Further, the compound (5) were evaluated for cytotoxicity screening against glioblastoma multiforme (GBM) cell lines (KNS42) with IC 50 (viability) of 0.84 μM. A docking examination was performed using compounds 5 and 6 to reveal the binding mode of the N-rimantadine indoleamides against mmpL3 (PDB ID: 6AJJ) and they were found to make the hydrogen bonds (HBs) with the Asp645 through their nitrogen of carboxamide and indole moieties, having similar binding modes with the previously identified carboxamides ICA-38.…”
Section: Indolesmentioning
confidence: 99%
“…[62] Jeyachandran et al have reported 2-(aryloxy methyl)aziridines ( 35) and 2-((3-aryl-1phenylallyloxy)methyl)aziridine (36) with MIC of 0.5 μg/mL having three-fold activity than standard drugs like ciprofloxacin and ethambutol as compared to ethambutol (MIC of 0.5 μg/ mL). [63] Chakravarty et al have reported anthracenyl phosphonate and π-conjugated acid cocrystals (37) with MIC of 1.56 μg/ mL, as active as ethambutol. These cocrystals have shown better anti-tubercular activity as compared to individual compounds due to hydrogen bonding interactions ( 31 P/ 1 H NMR) enhancing the hydrophobicity to penetrate the mycobacterial cell wall.…”
Section: Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these heterocyclic benzazoles, indole should not be undermined due to the potential anti‐TB activity as several research groups have focused on discovery of substituted indole as potent anti‐mycobacterial agents [28] . Recently, we have summarized the synthetic methodologies for the synthesis of indoles and their derivatives as anti‐mycobacterial agents, [29] wherein the synthesis of indole‐2‐carboxamides have been attained through (i) the carbonyl diimidazole (CDI) [30] or dicyclohexyl carbodiimide (DCC) [31] or 2‐(7‐aza‐1 H ‐benzotriazole‐1‐yl)‐1,1,3,3‐tetramethyluronium (HATU) [32] or 1‐ethyl‐3‐(3‐dimethylaminopropyl)carbodiimide (EDC) [33–39] . mediated coupling of several amines with indole‐2‐carboxylic acid.…”
Section: Designmentioning
confidence: 99%
“…[28] Recently, we have summarized the synthetic methodologies for the synthesis of indoles and their derivatives as antimycobacterial agents, [29] wherein the synthesis of indole-2carboxamides have been attained through (i) the carbonyl diimidazole (CDI) [30] or dicyclohexyl carbodiimide (DCC) [31] or 2-(7-aza-1H-benzotriazole-1-yl)-1,1,3,3-tetramethyluronium (HATU) [32] or 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC). [33][34][35][36][37][38][39] mediated coupling of several amines with indole-2carboxylic acid. Alternatively, ethyl indole-2-carboxylate have been treated with hydrazine hydrate followed by their substitution using carbonyl compounds.…”
Section: Designmentioning
confidence: 99%